2008
DOI: 10.1063/1.2997339
|View full text |Cite
|
Sign up to set email alerts
|

Whistler turbulence: Particle-in-cell simulations

Abstract: Two-dimensional electromagnetic particle-in-cell simulations in a magnetized, homogeneous, collisionless electron-proton plasma demonstrate the forward cascade of whistler turbulence. The simulations represent decaying turbulence, in which an initial, narrowband spectrum of fluctuations at wavenumbers kc∕ωe≃0.1 cascades toward increased damping at kc∕ωe≃1.0, where c∕ωe is the electron inertial length. The turbulence displays magnetic energy spectra that are relatively steep functions of wavenumber and are anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
139
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(153 citation statements)
references
References 31 publications
14
139
0
Order By: Relevance
“…Reasonable agreement between linear theory and observations is used to conclude in favour of one mode or another. The majority of studies cite KAWs as the most likely candidate, with whistlers typically (but not always [64]) being a poor fit to measurements [42,43,64,101,108,109,113,114]. Note that linear theory predictions are overwhelmingly determined using a uniform and constant global mean field, whereas recent observational results often employ space (or time)-dependent B loc 0 .…”
Section: Component (Variance) Anisotropymentioning
confidence: 99%
See 1 more Smart Citation
“…Reasonable agreement between linear theory and observations is used to conclude in favour of one mode or another. The majority of studies cite KAWs as the most likely candidate, with whistlers typically (but not always [64]) being a poor fit to measurements [42,43,64,101,108,109,113,114]. Note that linear theory predictions are overwhelmingly determined using a uniform and constant global mean field, whereas recent observational results often employ space (or time)-dependent B loc 0 .…”
Section: Component (Variance) Anisotropymentioning
confidence: 99%
“…Moreover, these explanations all presume that the fluctuations are dominantly wave-like. Although there is some numerical support for the wave-based explanations of variance anisotropy, for example in particle-in-cell simulations [113] and gyrokinetic simulations [101], it remains unclear whether strong turbulence has this property, at either MHD scales or sub-ion ones [115][116][117]; cf. §3b.…”
Section: Component (Variance) Anisotropymentioning
confidence: 99%
“…Some authors argue that it does not [83][84][85][86][87][88][89] and argue that kinetic Alfvén waves provide the observed steepening, but some of these observations have been brought into question [90]. Dispersion is sometimes invoked as an explanation for the steepening of the power spectrum at ion dissipation scales [55,[91][92][93][94][95] and whistler waves are also discussed in the context of forming the dissipation range at ion scales [92,[96][97][98]. The central issue to that question rests with the dissipation processes that remove energy from the turbulence and produce heat.…”
Section: Heatingmentioning
confidence: 99%
“…Many theories [e.g., Gary et al, 1994;Vocks et al, 2005;Saito and Gary, 2007] of the evolution of electrons from the Sun to the Earth suggest WWs scatter strahl electrons into the halo, which may explain the observed changes [e.g., Štverák et al, 2009] in the relative densities of strahl versus halo electrons. Theories have also suggested that WWs constrain the heat flux carrying electrons [e.g., Gary et al, 1994Gary et al, , 1999, e.g., strahl, and the halo/core electron temperature anisotropies [e.g., Vocks and Mann, 2003;Saito et al, 2008]. The core electrons have been observed to isotropize due to binary collisions [e.g., Salem et al, 2003], while halo electrons appear to be constrained by the whistler anisotropy and firehose instabilities in the slow solar wind [e.g., Štverák et al, 2008].…”
Section: Introductionmentioning
confidence: 99%